TRANSFORMATION OF EDUCATION IN ELEMENTARY SCHOOLS: UTILIZATION OF ARTIFICIAL INTELLIGENCE-BASED LEARNING MEDIA IN THE DIGITAL ERA - Mukti, Fajar Dwi (DIRASATUL IBTIDAIYAH, 2023)
The study titled "Educational Transformation in Elementary Schools: Utilizing Artificial Intelligence-Based Learning Media in the Digital Era" aims to elucidate the importance of artificial intelligence (AI) integration in supporting the digital education transformation in elementary schools. The research method employed is a literature review involving collecting and analyzing data from various previous studies, as well as comparing and synthesizing expert opinions. The research findings indicate that using AI-based learning media, such as puzzle makers, provides significant benefits in elementary education. AI can enhance personalized learning by analyzing the needs and abilities of each student. Puzzle maker media also enhances student engagement in problem-solving, enriches understanding of learning concepts, and develops cognitive skills and abilities. The significance of AI integration in supporting digital education transformation is reflected in its ability to provide a more personalized and adaptive learning experience. AI can optimize the learning process by monitoring students' individual progress and providing tailored learning recommendations. However, challenges such as adequate technological infrastructure, teacher skills in operating AI technology, and developing relevant content exist. Solutions to address these challenges involve improving infrastructure, providing teacher training, and developing high-quality content. In conclusion, AI integration in elementary education has a positive impact on enhancing the quality of learning and providing a better learning experience. By addressing challenges and implementing appropriate solutions, AI can be an effective tool in supporting the transformation of digital education and achieving better education in this digital era